Writing for design professionals : a guide to writing successful proposals, letters, brochures, portfolios, reports, presentations, and job applications for architects, engineers, and interior designers - 461286 Kliment, Stephen A. (New York : W.W. Norton)
Includes bibliographical references (p. 219-222) and index